1998
DOI: 10.1183/09031936.98.11020366
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for lower respiratory disease during 20 yrs among under 5 yr old children in Stockholm County: a population based survey

Abstract: Lower respiratory disease (LRD) is a common cause of hospitalization in infants, and episodes of obstructive LRD increase the risk for asthma later in life. The purpose of this study was to assess time trends and geographical variation of first time hospitalization for LRD among children in Stockholm County, Sweden. Data on first time admittance for LRD among children aged up to 5 yrs from 1973 through 1992 were obtained from the Stockholm County Council hospital discharge register, and population register dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Simultaneously with the decrease in hospitalizations for asthma, hospitalization rates of infants and young children for bronchitis with wheezing have been high. [3,[12][13][14] As expected, these fi gures estimated by fi rst admissions in the present study were nearly equal in the two study areas. The similar fi rst admission rates suggest that the differences in the salbutamol doses used in the emergency rooms of the study hospital caused no signifi cant confounding to our results.…”
Section: Discussionsupporting
confidence: 87%
“…Simultaneously with the decrease in hospitalizations for asthma, hospitalization rates of infants and young children for bronchitis with wheezing have been high. [3,[12][13][14] As expected, these fi gures estimated by fi rst admissions in the present study were nearly equal in the two study areas. The similar fi rst admission rates suggest that the differences in the salbutamol doses used in the emergency rooms of the study hospital caused no signifi cant confounding to our results.…”
Section: Discussionsupporting
confidence: 87%
“…During the study period, there was a 40% increase in the hospitalization rate, with a 100% increase in the youngest age group (27). However, among the children aged 2-4 y, no increase in rst-time admissions was observed.…”
Section: Discussionmentioning
confidence: 87%
“…Although hospital admissions data may not be the ideal outcome for assessing infectious disease, we believe that they represent a reasonably accurate measure of infectious load in the community. In a study of lower respiratory disease in Sweden, Wickman et al [29] concluded that the increased rate of hospitalisation in infants may reflect a true increase in the incidence of respiratory disease. However, the use of hospital admissions as a marker of common infections needs to be verified using alternative datasets.…”
Section: Discussionmentioning
confidence: 99%